Digital Supply Chain Practices and Firm Performance: The Mediating Role of Data-Driven Decision Making - Elshahawy, Rehab; Mostafa, Amany Mohamed; El Ezz, Moataz Abo (Engineering, Technology & Applied Science Research, 2026)
With the rapid advancement of digital technologies, Digital Supply Chains (DSC) have become critical to enhancing organizational productivity. The existing literature lacks integrated models that clearly explain the relationships among DSC practices, Data-Driven Decision-Making (DDDM), and Organizational Performance (OP). This study examines the effect of DSC practices on OP, with particular emphasis on the mediating role of DDDM. Drawing on the Resource-Based View (RBV), Dynamic Capabilities Theory, and Information Processing Theory, the study employs an online survey of 366 employees in Egypt’s food and beverage supply chain sector. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1. The findings indicate that DSC practices have a positive and significant effect on DDDM, which in turn substantially enhances firm performance. Moreover, DDDM serves as a mediating mechanism between DSC practices and OP, suggesting that the performance benefits of DSC resources are realized primarily through improved organizational decision-making processes.